Effect of long term consumption of graded levels of powdered stored Ocimum gratissimum supplementation on the weight performance in Wistar rats - Kunle, Ogungbemi; Taiwo, Ishola D.; Tomilayo, Ishola O.; Adebisi, Arowora K.; Funmilayo, Ilesanmi F. (International Journal of Scientific Reports, 2017)
Background: The influence of Ocimum gratissimum leaf supplementation on feed intake; weight change via growth performance of Wistar rats was investigated. Methods: A total of twenty (20) rats (average weight of 80 g±10 g), housed in a well-ventilated cages and given feed and water ad libitum for 2 weeks after which they were randomly allotted to four dietary treatments comprising 0%, 2.5%, 5% and 10%, of powdered stored Ocimum gratissimum leaf inclusion. Results: Group of rats fed with the lowest supplementation (2.5%) of Ocimum gratissimum showed significant increase (P< 0.05) in weekly feed intake than group fed with the highest supplementation (10%). While, there was no significant difference (P >0.05) between the groups fed with 0% and 5%. Also, the weight gain by the rats with 2.5% Ocimum gratissimum diet supplementation had highest weight gain which was significantly different to 10% supplementation and non-significantly different to 5% supplementation. Animals which received 2.5% of leaf of Ocimum gratissimum had the fastest growth rate, followed by those that received 5% and 10%. However, the control feed had higher body weight gain than 10% supplementation. The observable increase in the feed intake, weight gain and feed efficiency seen in the lowest supplementation level (2.5%) can be attributed to the spicing and seasoning of food with O. gratissimum and as such could also increase the palatability of the food. Furthermore, 2.5% has the highest dietary lipid which increases the palatability of food by absorbing and retaining flavor. Conclusions: It can be concluded that 2.5% O. gratissimum supplementation has a better palatability than other experimental diets which reflected on the performance characteristics of this treatment.